The Ilo’s Role in Protecting Domestic Workers in Indonesia Is Highlighted by The Ratification of Convention Number 189 of 2011 - Masruroh, Siti; Supriyanto, Agustinus (Balobe Law Journal, 2026)
Introduction: The 2020 annual report of the National Commission on Violence Against Women confirmed at least 34 cases related to domestic workers throughout 2019. Meanwhile, documentation of these cases by the National Network for Domestic Workers Advocacy (JALA PRT) states that between 2012 and 2019, there were more than 3,219 cases experienced by domestic workers, including psychological abuse (isolation and confinement), physical abuse, economic abuse (withholding of personal documents, unpaid wages, sick pay, unpaid holiday pay), and human trafficking.  Meanwhile, from 2017 to 2022, at least 2,673 cases of violence experienced by domestic workers did not decrease but instead increased. Therefore, the role of the ILO in Indonesia is quite important in preventing the continuation of this problem.Purposes of the Research: This study aims to determine and analyze the extent of legal protection for domestic workers provided by the Indonesian government and the role of the ILO (International Labor Organization) as an international organization that collaborates with the government, employers, and non-governmental organizations.Methods of the Research: This research uses a normative-empirical legal research method, which functions as a study of normative-empirical legal issues in the form of legal behavior products. Normative-empirical studies focus on the application of applicable legal provisions to every legal event that occurs in society to achieve that goal. This research begins with the applicable legal provisions in written form for each legal event in society, thus combining two stages of study. The first stage examines the applicable normative laws, and the next stage applies these laws to events that occur in society in order to achieve the selected objectives. Based on the above explanation, this research requires primary and secondary data.Results of the Research: The ILO, as the representative of the International Labor Organization, has done a lot to oversee and encourage the ratification of domestic worker protection and the immediate passing of the PPRT Bill. In this case, various projects have been carried out by the ILO to facilitate the realization of protection for domestic workers, one of which is by inviting cooperation with various groups from NGOs, employers, and the government. This includes providing socialization and training for domestic workers by inviting cooperation with JALA PRT. JALA PRT also has domestic worker schools in several major cities that provide education to domestic workers regarding the rights and obligations they should receive.